مصطلحات علم الأصوات النطقي عند سيبويه وابن جني بين التأصيل والاستعمال (مجلة الواحات للبحوث والدراسات, 2021)
The Research Was Divided Into Two Main Sections, Which Adopted In Its Division The Conceptual Dimension Provided By The Terminology; Came The Terms Of Each Branch Itself, But The Internal Arrangement - In Each Branch - Came Alpha; Synonyms. In One Entry, It Was Placed Next To Her What Was Contrary To Them In The Concept Such (Voiced) And (Voiceless). The Division Was As Follows: General And Phonetics Terms.      The Research Began By Introducing The Use Of SEBAWH And IBN JENNY To Define The Concept, And Then Rooting The Term, Especially When ALKHALEEL.Trying To Identify The Author Of The Term, Is It ALKHALEEL Or SEBAWH Or IBN JENNY? He Then Examined The Use Of The Term In Modern Linguistic Studies, Which Include Linguistic Dictionaries And Books, Defining The Relationship Between The Term And The Concept In Modern Usage. Keywords-  Terminology, Phonetics, Linguistics, SEBAWH, IBN JENNY